(untitled) (International Journal of Engineering and Computer Science, 2017)
Preserving privacy in social networks against neighborhood attacks is an initiation which uses the definition of privacy called K-anonymity. K-anonymous social network still may leak privacy under the cases of homogeneity and background knowledge attacks. To overcome, we find a place to use a new practical and efficient definition of privacy called G-anonymity. In this paper, we take a step further on preserving privacy in collaborative social network site by developing a site using the G-anonymity to improved user privacy on the social media for unaware and illiterate users. Testing was performed using five users and from the users comment; it was observed that the system is 70% efficient for their usage which is better than the other existing systems.